33 Histologic Variants of Urothelial Carcinoma: A Retrospective Study of Cystoscopic Biopsies - Vikram Verma; Kamakshi Goswami; K C Goswami; Arvind Khajuria; Aneeta Singh (Dr. Annil Mahajan, 2022)
Background: Urothelial carcinoma is the most common malignancy of the urinary tract.Many variants of infiltrating urothelial carcinoma have been described which are aggressive tumors associated with advanced disease at presentation and are often managed with neoadjuvant chemotherapy and radical cystectomy.Material and Methods: 56 TURBT specimens received in the department of Pathology, ASCOMS and hospital were included in the study.All the specimens were fixed in 10% buffered formalin,paraffin sections and stained with Hematoxylin -Eosin stain.Histological analysis of the slides was carried out.Relevant clinical data regarding age and sex was recorded.Results:56 TURBT biopsies were analyzed.Male to female ratio was 3.6:1.Mean age of patients was 60.79 years with a range of 35- 90 years.Out of 56 cases of urothelial carcinomas,57.14% were high grade and 42.85% low grade.60.71% carcinomas showed pT1,32.14% pT2 and 7.14% pTa stage.Pure urothelial carcinoma was noted in 69.64%, with squamous differentiation in 19.64%,glandular differentiation in 5.35%.One case each(1.78%) of sarcomatoid,plasmacytoid and nested variant was seen.All the infiltrating urothelial carcinomas with variant morphologies presented in pT2 stage except 3 tumors with squamous differentiation in pT1.Conclusion: Urothelial carcinoma is a common malignant tumor of urinary bladder